EFFECTIVENESS OF CSR COMPANION COMMUNICATION RELATIONSHIP TOWARDS PROGRAM SUCCESS RATE (CASE STUDY ON CSR PROGRAM TO REDUCE STUNTING PT PLN INDONESIA POWER UBP JERANJANG WEST LOMBOK) - Febriani, Baiq I'ing Nadia; Fajarica, Shinta Desiyana; Budiyanto, Teguh; Dwiputri, Tristiayu Permata (International Journal of Social Service and Research, 2024)
Stunting represents a developmental impairment in children resulting from malnutrition, recurrent infections, and inadequate psychosocial stimulation. Addressing this issue requires comprehensive strategies and concerted efforts. As part of the initiative to reduce stunting prevalence, PT PLN Indonesia Power UBP Jeranjang has implemented a Corporate Social Responsibility (CSR) program aimed at alleviating stunting through training and supplementary feeding (PMT), in collaboration with CSR facilitators from the company. Effective communication by these facilitators plays a crucial role in the program's success. Therefore, this study aims to investigate the existence of a positive and significant relationship between the effectiveness of CSR facilitator communication at PT PLN Indonesia Power UBP Jeranjang in West Lombok and the success of the CSR program in reducing stunting. The research adopts a quantitative approach. Data were gathered through questionnaire and document analysis. Data analysis employed Spearman Rank correlation and descriptive statistics. The findings indicate a significant positive correlation between CSR facilitator communication effectiveness and program success, with a significance level of 0.002 and a correlation coefficient of 0.383. Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.